2013
DOI: 10.1155/2013/620531
|View full text |Cite
|
Sign up to set email alerts
|

Plucked Human Hair Shafts and Biomolecular Medical Research

Abstract: The hair follicle is a skin integument at the boundary between an organism and its immediate environment. The biological role of the human hair follicle has lost some of its ancestral importance. However, an indepth investigation of this miniorgan reveals hidden complexity with huge research potential. An essential consideration when dealing with human research is the awareness of potential harm and thus the absolute need not to harm—a rule aptly qualified by the Latin term “primum non nocere” (first do no har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Recently, the human hair follicle and its stem cell reservoir have received growing attention due to their potential for applications in the field of regenerative medicine (Mistriotis & Andreadis, ; Schembri, Scerri, & Ayers, ). The hair follicle contains a variety of cellular components: epithelial cells from the hair matrix and the bulge region, the outer root sheath (ORS) in particular, mesenchymal cells from the dermal papilla and dermal sheath, plus several pools of epithelial, mesenchymal, and melanocyte stem cells (McElwee & Sinclair, ; Paus & Cotsarelis, ; Rompolas & Greco, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the human hair follicle and its stem cell reservoir have received growing attention due to their potential for applications in the field of regenerative medicine (Mistriotis & Andreadis, ; Schembri, Scerri, & Ayers, ). The hair follicle contains a variety of cellular components: epithelial cells from the hair matrix and the bulge region, the outer root sheath (ORS) in particular, mesenchymal cells from the dermal papilla and dermal sheath, plus several pools of epithelial, mesenchymal, and melanocyte stem cells (McElwee & Sinclair, ; Paus & Cotsarelis, ; Rompolas & Greco, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a skin biopsy is required in order to obtain intact HFs, whereas hair plucking is a less invasive technique. Moreover, it has been demonstrated that plucked hairs retain most epithelial structures, maintain the integrity of the outer root sheet and also contain stem cells [ 46 ]. Finally, due to the small size of our samples, particularly that of the replication sample, we considered advisable to exclude from the present study indels and sex chromosomes, and limit ourselves to reporting, in very general terms, differential findings between HFs from frontal and occipital scalp areas.…”
Section: Discussionmentioning
confidence: 99%
“…Plucking is used in medical research and for obtaining a surrogate tissue in drug development. 12 The analysis of plucks is also important in forensic science. 13 The advantages of plucking are that collection is fast, can be done at clinical scale, is less invasive than biopsies and yields tissue from a single hair follicle without any surrounding tissues.…”
Section: Pluckingmentioning
confidence: 99%
“…A punch biopsy is a rapid and reproducible method to obtain uniform shaped skin samples containing intact follicles. 12,20,21 In this technique, skin is extracted using a disposable or sterilizable punch. Care must be taken to ensure the biopsy contains both the subcutaneous fat and the entire follicle unit within.…”
Section: Biopsymentioning
confidence: 99%